Regulation of Huntingtin Gene Expression by miRNA-137, -214, -148a, and Their Respective isomiRs - Kozlowska, Emilia (Molecular Diversity Preservation International (MDPI), 2013)
With the advent of deep sequencing technology, a variety of miRNA length and sequence variants, termed isomiRNAs (isomiRs), have been discovered. However, the functional roles of these commonly detected isomiRs remain unknown. In this paper, we demonstrated that miRNAs regulate the expression of the HTT gene, whose mutation leads to Huntington’s disease (HD), a hereditary degenerative disorder. Specifically, we validated the interactions of canonical miRNAs, miR-137, miR-214, and miR-148a, with the HTT 3′UTR using a luciferase assay. Moreover, we applied synthetic miRNA mimics to examine whether a slight shifting of miRNA seed regions might alter the regulation of the HTT transcript. We also examined miR-137, miR-214, and miR-148a isomiRs and showed the activity of these isoforms on reporter constructs bearing appropriate sequences from the HTT 3′UTR. Hence, we demonstrated that certain 5′-end variants of miRNAs might be functional for the regulation of the same targets as canonical miRNAs.